2003
DOI: 10.1186/1472-6831-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge and behavior among male health sciences college students in Kuwait

Abstract: BackgroundHealth auxiliary personnel have an important role in oral health promotion when they graduate and start working in the health care system. This study aims to find out oral health knowledge and oral health behavior of male Health Sciences College students.MethodsA questionnaire was distributed to all students at the male Health Sciences College in Kuwait (N = 153) during the academic year 2001/2002. The students filled the anonymous questionnaire in the class after the lecture. The response rate was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
124
5
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(161 citation statements)
references
References 20 publications
27
124
5
5
Order By: Relevance
“…Behavior is an outcome measure when an action is sustained. Therefore, adequate oral health knowledge, attitude and behavior are very important for the improvement of patient's oral health [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behavior is an outcome measure when an action is sustained. Therefore, adequate oral health knowledge, attitude and behavior are very important for the improvement of patient's oral health [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The attitude of an individual towards performing a particular behavior may be used as a predictor of certain behavioral outcomes [5,6]. Regarding oral health, it has been shown that those with high concern for their oral health are more likely to partake in healthy oral health behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2] Oral diseases qualify as one of the foremost public health dilemma owing to their higher prevalence in general population. 3 Poor oral hygiene is the main leading cause for the development of oral diseases which heavily affect general health.…”
Section: Introductionmentioning
confidence: 99%
“…[38] However, many of them have a number of complications, which significantly reduces their therapeutic properties. Although the oral cavity, teeth, and gums are isolated zones, continuous moistening with the saliva causes quick washing the medication into the lower parts of the digestive canal, which requires repeated medication administration.…”
Section: Application Of Films In Medicinementioning
confidence: 99%